Expanding Capacity on New Generation of Seasonal and Sub seasonal Forecasts in West Africa and the Sahel - Houngnibo, Mandela C M; Kiema, Arsène; Tanimoune, Laouali I; Halidou, Tinni Seydou; Alhassane, Agali; Ali, Abdou; Segnon, Alcade Christel; Zougmore, Robert Bellarmin (2025)
This report presents the activities, outcomes, and recommendations of the 2025 training series on the “New Generation of Seasonal and Sub-seasonal Forecasts in West Africa and the Sahel.” The sessions were held online from April 10 to 11, 2025, as a prelude to the Regional Climate Outlook Forum (RCOF) for West Africa and the Sahel, and in-person from June 23 to July 11, 2025, at the AGRHYMET Regional Climate Center in Niamey, Niger. The online refresher training served as a review session for previously trained experts, conducted ahead of the seasonal forecast exercises to reinforce the use of the WAS_S2S tool, a modern forecasting platform developed under the AICCRA project. The in-person session specifically targeted representatives from the National Meteorological Services (NMSs) of Guinea, Togo, and Sierra Leone, who were unable to attend the inaugural training in October 2024. The in-person workshop combined theoretical lectures with intensive hands-on exercises, during which participants completed country-focused mini-projects. These capacity-building activities strengthened the ability of West African National Meteorological Services (NMSs) to produce objective, reproducible, and operational seasonal forecasts using the WAS_S2S tool.